ABOUT ONE ASPECT OF STATE SUPPORT FOR FARMS - Paata Koghuashvili; Joseph Archvadze; Nikoloz Chikhladze (ეკონომიკური პროფილი, 2022)
Agriculture, despite the relative stabilization of recent years, is still the weakest link in the Georgian economy. This is evidenced by the country's low level of self-sufficiency in many types of agricultural products (for wheat - 22%, for corn – 74%, for vegetables – 61%, for meat - 51%) and its high dependence on imports. In the first 9 months of 2022 alone, the negative balance in foreign trade in agricultural and food products amounted to 385.8 million US dollars, which negatively affects both the macroeconomic state of the economy and the country's exchange rate.